2018
DOI: 10.1177/1045389x18806397
|View full text |Cite
|
Sign up to set email alerts
|

3-Degree-of-freedom electromagnetic vibration energy harvester with serially connected leaf hinge joints

Abstract: This article presents a new design method of a planar 3-degree-of-freedom serial manipulator-type electromagnetic vibration energy harvester in which any desired ratio of power peaks and three target resonant frequencies can be specified arbitrarily. The design of the harvester aims to achieve minimum difference between the power peaks generated at target frequencies. The geometrical positions of three normal modes are first determined and the corresponding stiffness matrix of the harvester is found. Second, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In [55], a 3 degree of freedom (3-DOF) serial manipulator-type harvester was presented. The device was composed of a coil holder and three serially connected leaf hinge joints with a proof mass attached to the free end.…”
Section: Othersmentioning
confidence: 99%
“…In [55], a 3 degree of freedom (3-DOF) serial manipulator-type harvester was presented. The device was composed of a coil holder and three serially connected leaf hinge joints with a proof mass attached to the free end.…”
Section: Othersmentioning
confidence: 99%
“…Jang et el [4] showed that there exist relatively simple geometrical relationships between vibration axes of in-and out-of-plane modes. Recently, some researchers [5]- [7] presented design methods of planar vibration system by use of geometric properties of in-plane modes. Park and Choi [8] utilized geometric properties of out-of-plane modes to design energy harvester with desired resonant frequencies.…”
Section: Aaamentioning
confidence: 99%
“…Kim et al [1] utilized those advantages to develop a design method of a 3-DOF vibration system for prescribed work ratios. This method was applied to the design of a vibration energy harvester composed of serial linkages [7], [8]. However, since a rigid body has 6-DOF in space, it may be said that a 6-DOF spatial system is more desirable for high efficiency.…”
Section: Introductionmentioning
confidence: 99%